The recognition of the simbol of the test mark by application of the neural network model - A.P. Korobeinikov; N.N. Sadovoy (Advanced Engineering Research)
The variants of answers are registered by cross (mark) in many test forms. The mark must be put on definite field of the test form. It is necessary tj employ the system of pattern recognition for corrective encoding this field. This system of pattern recognition must be stable against various distortions and interferences in the field of mark. This systems must employ the combination of neural network and one of the methods of the pattern recognition theory.